Molecular genetic signatures of head and neck squamous cell carcinoma and their changes induced by proton irradiation - Enar D. Jumaniyazova; Anastasia V. Lokhonina; Alexandra V. Sentyabreva; Anna M. Kosyreva (RUDN Journal of Medicine)
Head and neck squamous cell cancer (HNSCC) is the seventh most common malignancy in the world. The overall incidence of HNSCC is increasing and is projected to increase by about 30 % annually by 2030. Clinically, HNSCC is characterized by an aggressive course: rapid local spread, resistance to various methods of antitumor treatment, and frequent recurrences. Despite improvements in diagnostic and therapeutic approaches over the last two decades, mainly due to the respective heterogeneity of these tumors, the outcomes of patients with HNSCC have not shown significant improvements, especially for patients with late TNM stage, with an overall five-year survival rate of 50 %. Approximately 75 % of HNSCC patients are treated with radiation therapy either alone or as part of a comprehensive treatment regimen. To date, one of the main ways to improve the efficacy of radiation therapy in HNSCC is considered to be a combination of maximum allowable increase of radiation dose in the target tumor and reduction and minimization of such dose in the surrounding healthy tissues. From this point of view, proton therapy (PT) has a pronounced advantage over various types of photon irradiation. Despite the growing interest of scientists in PT, studies aimed at identifying molecular and genetic changes induced by PT are scarce, while in our opinion they are very important for understanding intracellular mechanisms leading either to tumor cell destruction or to the development of radioresistance. This review summarizes the available knowledge on the changes in the main signaling pathways of HNSCC tumor cells under the influence of PT.